Die Einbeziehung der lokalen Kaltluft in Planungsentscheidungen - Schirmer, Hans (Raumforschung und Raumordnung | Spatial Research and Planning, 2003)
The new guideline of the German Association of Engineers (VDI) no. 3887, sheet 5 considers the processes of the development and flow-off of cold air that are important for urban and regional planning. It evaluates the impacts of planning interventions on air hygiene, human beings, plants, traffic and settlement planning. Furthermore it gives reasons for the designation of priority areas for climate protection in regional plans.